The Impact of Gut Microbiota on Post-Stroke Management - Zhao, Junyi; Liu, Siyu; Yan, Jingyi; Zhu, Xinzhou (Frontiers in Cellular and Infection Microbiology, 2021)
Ischemic stroke is one of the major issues in public health. The commensal gut microbiota has been discovered to influence brain activity through a bidirectional communication pathway. The interplay of gut microbiota and brain does not only occur in physiological status but also in distinct pathological conditions. Here we summarized recent advances on the interactions between ischemic stroke and gut microbiota actions. We emphasized on the impacts from gut microbiota on the main concerns during post-stroke management, including immune responses, body temperature, blood glucose, blood pressure, oxygen and hydration. We assumed that investigations on specific bacteria species and metabolites in gut microbiota could provide potential therapeutic opportunities for stroke recovery.